Understanding the meaning and symbols of animals in visual artwork : a case study of five selected works in the SI + SA 2020 exhibition / Rosmidahanim Razali ... [et al.] - Razali, Rosmidahanim; Abdul Razak, Ruzamira; Saad, Mohd Nafis; Nazrin, Nizar; Ramli, Ishak; Ismail, Issarezal (Universiti Teknologi MARA, Perak, 2021)
Visual artwork is a platform to convey the meaning of the theme chosen in producing the work. However, it is difficult to understand the meaning through the symbols highlighted by the artist. Based on that situation the objective of this study is to collect information on visual artworks that apply animal symbols in the SI + SA 2020 exhibition. Five artists have been identified using animal symbols in the production of their artwork. This study is based on qualitative research approach using four types of data; namely the study of literature that explains the meaning and symbol of animals from the point of view of previous scientific writing. The second method is based on information obtained from the artist statement in the SI + SA 2020 Exhibition catalogue. The third method, the researcher interviewed (partially structured) five artists who have been selected using animal symbols in their artwork. The fourth method is to use the theory of Edmund Burke Feldman (1994) which has four stages in the theory, namely description, analysis, interpretation and evaluation. Triangulation (qualitative) studies are conducted to obtain more data and the validity of the findings obtained. The result shows an understanding of the meaning and symbol varies according to the needs of the individual or society. Some artists associate symbols in the context of personal experiences or observations of an event. Symbols can also carry meaning in the context of social sciences. In the production of their artworks, the use of symbols is a method to convey a message and an easier way to communicate. Conclusion clearly shows that the meaning of these animal symbols depends on different personal perceptions - different from the references studied. It can reveal to the general public that the use of animal symbols applied in the work can carry various meanings. Researchers suggest for future studies to conduct comprehensive research on the use of symbols in contemporary visual arts Malaysia.